2020
DOI: 10.3390/ijerph17165812
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Work-Related Physical Activity and Leisure-Time Physical Activity on the Risk of Diabetes in Korean Adults

Abstract: The object of this study was to examine the effects of domestic and work-related physical activity (DWPA) and leisure-time physical activity (LTPA) on the risk of diabetes, by categorizing fasting blood glucose (FBG) levels into normal, Impaired Fasting Glucose (IFG), and diabetes. The sample consisted of 4661 adults aged 30 years or above, and was chosen from the 2017 Korean National Health and Nutrition Examination Survey (KNHANES) data. Of all the subjects, 14.6% engaged in high-intensity DWPA and 6.25% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The results also showed that the studied population in La Guajira complieds with the recommended physical activity, which could be a contributing factor to the prevention of pathologies associated to cardiovascular diseases and type 2 diabetes ( 2 , 40 , 43 ). Further to this, proposed population strategies, that include the creation of bio-health spaces with mechanical elements that facilitate physical activity, have been made with the aim to encourage an increase in physical activity ( 45 ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The results also showed that the studied population in La Guajira complieds with the recommended physical activity, which could be a contributing factor to the prevention of pathologies associated to cardiovascular diseases and type 2 diabetes ( 2 , 40 , 43 ). Further to this, proposed population strategies, that include the creation of bio-health spaces with mechanical elements that facilitate physical activity, have been made with the aim to encourage an increase in physical activity ( 45 ).…”
Section: Discussionmentioning
confidence: 58%
“…These results are similar to those found by this study, as when disaggregating the results of the ethnic and non-ethnic groups during the logistic regression analysis, it was observed that within the ethnic group, the lower social classes (stratum 2) complied more with the physical activity recommendations than those in a higher social class (stratum ≥ 3). A possible explanation to this phenomenon is the jobs that these individuals may have; manual jobs may have higher occupational physical activity demands when compared to non-manual jobs, with leisure time increasing in the same way it does for the groups with a higher income ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leisure-time and transport PA is associated with a decreased risk of diabetes 16 , 23 . However, the existing evidence for the association between work PA and diabetes risk is limited and inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large prospective cohort study showed that participation in resistance exercises is associated with reduced risk of developing diabetes by 34% over 18 years 15 . However, little is known whether non-leisure PA such as work PA and transport PA would affect the risk of type 2 diabetes 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Handling a chronic disease comes with facing certain limitations. Moderate -to high-intensity household activities were related to an increased risk of diabetes (Oh, 2020). Carbohydrate, fat, protein and overall calorie intake are some of the modifiable risk factors diabetic patients have to keep an eye on, making them more selective of their food choices.…”
Section: Health Challengesmentioning
confidence: 99%